Biomarkers of in vivo platelet activation in thoroughbreds during their first long-term training - Miglio, Arianna; Falcinelli, Emanuela; Mezzasoma, Anna Maria; Busechian, Sara; Rueca, Fabrizio; Gresele, Paolo; Antognoni, Maria Teresa (Frontiers in Veterinary Science, 2024)
Physical exercise has an activating effect on platelet function, different in trained and untrained subjects, depending on the type of exercise and training status. In humans, soluble P-selectin (sP-sel) and platelet-derived extracellular vesicles (PEVs) are considered reliable markers of in vivo platelet activation during exercise. In untrained humans they increase after transient physical exercise, whereas long-term training induces a decrease of their resting levels due to an improved ability to adapt to changes in hemodynamics. The aim of this study was to assess whether circulating sP-sel and PEVs levels may represent useful markers to explore in vivo platelet function in never-trained Thoroughbreds during their first 4-months incremental training. Twenty-nine clinically healthy untrained Thoroughbreds (17 males and 12 females) were enrolled. All horses were trained with the same training schedule (90 days). Blood samples were collected on the day of the beginning of the training program (T0), 30 days (T30), and 90 days (T90) after its incremental increase to quantify platelet count, sP-sel and PEVs. Statistical analysis was performed by RM one-way analysis of variance with the Geisser-Greenhouse correction. Soluble P-selectin tended to increase at T30 compared with T0, while T90 values returned to baseline values. Significant higher circulating levels of PEVs CD61+/AnnV+ were observed at T30 and T90 compared to baseline confirming platelet hyperactivity. The detection and quantification of sP-sel and PEVs in equine racehorses during the training period seems to be a promising tool to study exercise-induced primary hemostatic changes and could provide an important marker regarding exercise selection.